Klimaproblematikken som global fortælling - Mikkel Fugl Eskjær (Akademisk Kvarter, 2011)
Mikkel Eskjær presents us with three different narratives about the climate issue in The climate problematic as a global narrative: Medialization of a late modern risk: a) different sociological scenarios that give us an understanding of the causes and consequences of climate change, b) the media's narratives, their character, and content, and c) popular culture representations in the form of disaster narratives about the climate. Those narratives are helping to create the meanings that climate issues get at a global level.